2016
DOI: 10.1016/j.supflu.2015.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Sterilization of PMMA microfluidic chips by various techniques and investigation of material characteristics

Abstract: a b s t r a c tThe sterilization of microfluidic chips is a vital step of the fabrication process prior to the customer use in biomedical applications. The aim of this study was to analyze the influence of different sterilization techniques and to compare the characteristics of the material before and after sterilization of polymethylmethacrylate (PMMA) microchips. For this, supercritical carbon dioxide (SC-CO 2 ) along with standard sterilization methods such as ultraviolet (UV), heat (autoclaving), ethylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 24 publications
(34 reference statements)
0
19
0
Order By: Relevance
“…All samples had similar spectra before and after the different decontamination techniques. Further, the formation of new absorption bands was not observed, nor was there any loss of signal, which suggests that there was no chemical change of the material's surface structure . Farrugia et al found some band flattening for ATR/FTIR using a longer period of decontamination (10 min) and sonication with 70% ethanol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples had similar spectra before and after the different decontamination techniques. Further, the formation of new absorption bands was not observed, nor was there any loss of signal, which suggests that there was no chemical change of the material's surface structure . Farrugia et al found some band flattening for ATR/FTIR using a longer period of decontamination (10 min) and sonication with 70% ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the formation of new absorption bands was not observed, nor was there any loss of signal, which suggests that there was no chemical change of the material's surface structure. 29 Farrugia et al 13 found some band flattening for ATR/FTIR using a longer period of decontamination (10 min) and sonication with 70% ethanol. Therefore, it may be that the time of decontamination used was not long enough (1 min) in this study to cause changes in the chemical structure of the molecules of the resins tested.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, we designed a polymethyl methacrylate mold for a 24-well plate. This mold is reusable and can be sterilized using different strategies such as supercritical carbon dioxide, hydrogen peroxide gas plasma, ethylene oxide, and even γ-irradiation [31,32]. Furthermore, the mold produced more reproducible and homogeneous scratches in contrast with gaps made using only a pipette tip.…”
Section: Plos Onementioning
confidence: 99%
“…The sterilized content would then be flushed out before replenishing the local niche with “fresh” cells. Alternative methods of sterilization rely on one or a combination of physical (autoclaving, UV light) and chemical treatments (ethanol, ethylene oxide, hydrogen peroxide,..) (Skaalure, 2008 ; Horst et al, 2009 ; Zhang et al, 2014 ; Yavuz et al, 2016 ), and could be applied to SLMC, for larger scales (e.g., bioreactors,..), depending on the tolerance of the materials used. Ultimately, in order to limit the risk of the occurrence of adverse events, we suggest the periodic replacement of the cells.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%